b-Smarandache tm2 Curves of Biharmonic New Type b-Slant Helices according to Bishop Frame in the Sol Space Sol3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study b-Smarandache tm(2) curves of biharmonic new type b-slant helix in the Sol(3). We characterize the b-Smarandache tm(2) curves in terms of their Bishop curvatures. Finally, we find out their explicit parametric equations in the Sol(3)
Keywords: new type b-slant helix; Sol space; curvatures